Smart parking guidance system using 360 ̊camera and Haar-Cascade classifier on IoT system - Salma (Kulliyyah of Engineering, International Islamic University Malaysia, 2019)
Nowadays, smart parking guidance system is a crucial research for people's convenience where the integrating concept of IoT that include hardware and software with the connection of internet for image or video processing technology. It is a powerful application which made up a complete smart parking system. The main objective of this research is to develop and analyze on a smart parking guidance system where current available system was compared to this new proposed system. Limited parking space has become serious issue since the number of Malaysia's populations using car keep increasing. Some companies, shopping malls and other public facilities have already deployed smart parking systems on their buildings. However, there are still a lot of buildings that do not possess it because the system requires a lot of investment, where huge parking spaces need higher cost to install sensors on each parking lot availability. In addition, cameras are costly and lower in reliability. The proposed smart parking guidance system in this research was depending on a 360° camera that was modified on Raspberry Pi camera module and 360o lens that process with De-Warping techniques for the normal view rather than 360-degree view and Haar-Cascade classifier. The image and video processing was performed by Open CV and python program to detect the available parking space. The cloud firebase was used to update data where users could access the parking space availability by android mobile phone specifically at a closed parking space. A single 360° camera was replaced several sensors and cameras which were implemented on traditional parking guidance system. An analysis was done on the performance of the system where it can detect the parking availability with 99.74% accuracy. It shows better improvement than the conventional system including reliability and cost for the smart parking guidance system.